Compósitos reticulados de Eversa® Transform e nanopartículas magnéticas como biocatalisadores para a síntese de biodiesel em reator de fluxo em vórtices - Miranda, Letícia Passos (Universidade Federal de São Carlos, 2020)
The enzymatic production of biodiesel is a promising alternative to the conventional production by the alkaline route in a homogeneous medium. The enzymatic process allows using raw material with any concentration of free fatty acids due to the specificity of the lipases and lower energy consumption, because the enzymes act at mild temperature conditions. The liquid formulations of lipase from Thermomyces lanuginosus, Eversa® Transform and Eversa® Transform 2.0, were launched by Novozymes A/S to be used in the biodiesel production in their free forms. After characterizing the two formulations, it was identified that both are very similar, differing in the greater thermal stability of the second formulation, which is used to give segment to this work. The immobilization of enzymes can improve theior performance in the production of biodiesel, in addition to enabling the recovery and reuse of the biocatalyst. In this work, Eversa lipase was immobilized by the technique of cross-linked enzyme aggregates (CLEAs), a simple, economical and unsupported technique, capable of generating insoluble biocatalysts with high volumetric activity and improved stability. The preparation conditions were optimized in order to improve the properties of the biocatalyst. The nature of the precipitant and concentration of the crosslinking agent were evaluated. To improve the crosslinking step, bovine serum albumin (BSA), soy protein (SP) or polyethyleneimine (PEI) were co-precipitated and evaluated as co-feeders and additives. Starch (later enzymatically degraded) was used as a porogenic agent to reduce the diffusion limitations of the substrate. Magnetic silica nanoparticles functionalized with amino-octyl groups (MNPS) were also used to simplify the handling of CLEA, which are incorporated into the CLEAs by inter and/or intra crosslinks particle-enzyme with glutaraldehyde as bifunctional agent, but a great percentage of enzyme could also to be adsorbed on the nanoparticle surface before the aggregation step. The best CLEA was prepared using PEI, starch and MNPS (Eversa m-CLEA). Under these conditions, the biocatalyst showed an immobilization yield of 98.9%, recovered activity of 30.1%, a porous structure, and a thermal stability at 70°C around 40-fold higher than that of the free enzyme. In the transesterification reaction of refined soybean oil with anhydrous ethanol (molar ratio oil/ethanol 1:6), the best performance obtained was using 12 Uest/oil of Eversa m- CLEA at 40ºC. A mass yield of 89.8% of fatty acid ethyl esters (FAEE) was found after 12 h of reaction, while the soluble enzyme required 48 h of reaction to give the same yield. A caustic polishing step of the product yielded a biodiesel containing 98.9 wt.% of FAEEs and a content of free fatty acids (FFAs) below 0.25 wt.%, meeting the international standards of a biodiesel to be commercialized as biofuel. The immobilized biocatalyst could be reused for at least five cycles of 12 h, maintaining 89.6% of the first-cycle mass yield, showing the efficient recovery of the catalyst by applying an external magnetic field. From an experimental design (DCCR)23 , it was possible to define a range of optimized values to produce enzymatic biodiesel using also Eversa m-CLEA, however in the transesterification of raw materials oil, degummed soy oil, and hydrated ethanol. At a molar ratio oil/ethanol of 1:6, 4 Uest/oil at 40 ºC, a mass yield of 81.45 wt.% of FAEEs, with a FFAs content of 3.9 wt.% was obtained after 24h of reaction. After a caustic polishing, a yield of 89.88 wt.% of FAEEs with a FFAs content of 0.17 wt.% was obtained. The use of Eversa m-CLEA, a biocatalyst that is easy to recover and reuse, together with unrefined raw materials with lower added value, is a promising combination to contribute to the economic viability of the enzymatic route, aiming to make it competitive to the traditional alkaline route.
Crosslinked composites of Eversa® Transform and magnetic nanoparticles as biocatalysts for the synthesis of biodiesel in a vortex flow reactor
Keywords: Lipases; Eversa; Cleas magnéticos; Imobilização; Etanólise; Biodiesel; Magnetic cleas; Immobilization; Ethanolysis; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA